MORPHOLOGICAL OVERLAP OF FISH COMMUNITY IN VAMANAPURAM RIVER, SOUTH KERALA - Kingston, S. David; Arun, L. K.; Vijverberg, Koos; Natarajan, P. (Journal of Indian Fisheries Association, 2007)
The morphological characteristics and overlap of fish community inVamanapuram River have been studied in detail. In the 12 study sites, 19 fish species were encountered. Based on the body shape, four different types are apparent. The elongate bodied fishes (RBD < 1.5) like Hemiramphus xanthopterus and Xenentodon candia are grouped under one category. The deep bodied fishes (RBD > 3.5) like Puntius filamentosus, P. ticto, P. vittatus, P. melanampyx, P. sarana, Etroplus maculatus and E. suratensis come under a separate category. Fishes with round to square cross section like Garra mullya and Glossogobius giuris form a separate group. AU the other species are grouped as generalized bodied fishes. The morphological overlap studied for the Vamanapuram fish community showed that out of 190 combinations, 30 combinations have high overlaps ( > 67). P. melanampyx has maximum number (6) of high overlaps. Puntius spp., which constituted 49.5o/o of the total population, have a mean morphological overlap of 52o/o. The morphological overlap of fish species in relation to the trophic structure is discussed in detail.Keywords: Vamanapuram River, morphology, fish community,morphological overlap, competition